2012
DOI: 10.4155/tde.11.152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acyclovir Cream and Gel Formulations for Transdermal Iontophoretic Delivery

Abstract: Background: Efficient iontophoretic transdermal delivery of hydrophilic drug molecules requires selection of appropriate aqueous formulation. In this study, oil/water cream and gel formulations were investigated for iontophoretic transdermal delivery of acyclovir (ACV), a model hydrophilic small-drug molecule, across hairless rat skin on Franz diffusion cells. Results: Iontophoresis (0.2 mA/cm2) enhanced ACV delivery from both 5% cream (pH 6.8) and 4% gel (pH 11) formulations. However, sixfold higher drug leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Showed the most prolonged local analgesic effects and enhanced local anesthetic action (Kang & Shin, 2012). Acyclovir Showed enhanced iontophoretic transdermal delivery of acyclovir (ACV), a model hydrophilic smalldrug molecule, across hairless rat skin on Franz diffusion cells (Siddoju et al, 2012).…”
Section: Vancomycinmentioning
confidence: 99%
“…Showed the most prolonged local analgesic effects and enhanced local anesthetic action (Kang & Shin, 2012). Acyclovir Showed enhanced iontophoretic transdermal delivery of acyclovir (ACV), a model hydrophilic smalldrug molecule, across hairless rat skin on Franz diffusion cells (Siddoju et al, 2012).…”
Section: Vancomycinmentioning
confidence: 99%
“…Rashes or other serious side effects can occur when a more active ingredient penetrates into the skin [2]. Various controlled drug-delivery systems, such as microcapsules, microspheres, nanoemulsion, liposomes and niosomes, have been investigated in order to maximize the duration of active ingredients being present either on the epidermis or within skin layers, while minimizing their transdermal penetration into the body [3][4][5][6]. However, the release rate of active drugs from microcapsules cannot be controlled once the capsule wall is ruptured.…”
mentioning
confidence: 99%
“…37 A number of studies have been reported in the literature where VDCs have been employed for testing the drug release and/or permeation from acyclovir topical formulations. [38][39][40][41][42][43] Considering the advantages of immersion cells, we decided to study the IVRT of acyclovir cream formulations by using immersion cells. We initially studied the effect of test variables such as type of membrane, stirring speed, media temperature, media volume, and cell size on the acyclovir release from its marketed cream formulation.…”
Section: Discussionmentioning
confidence: 99%